The Epidemiology of Unintentional Home Injuries among Children Aged 0 – 14 Years in Assiut Governorate, Egypt: A Community-Based Cross-Sectional Study - GadAllah, Ahmed Mohmed (Journal of medical and pharmaceutical sciences, 2020)
The change in the epidemiological pattern of child mortality, the significant progress in combating infectious diseases and the increased risk of injuries to create a new vision for the rate of childhood injuries and deaths around the world because of the serious risk it poses, with injuries killing 5 million people each year, And that most of these injuries occur in and around the home where children spend at this age stage most of their time at home. So I focused in this research on this age stage in one of the largest governorates of Upper Egypt, which is Assiut.Objective: To study the magnitude and pattern of unintentional home injuries in children aged 0 – 14 years and to assess the environmental risk associated with home injuries.Methods: A community-based, cross-sectional study was conducted in 2018, on a rural population in Assiut governorate, Egypt. The total sample of children was selected from 500 households by systematic random sampling. Data were gathered using a predesigned, well-structured questionnaire from both the parents and children.Results: Of 1337 children, the prevalence of home injury was found to be 43.8% in the last 1 year, significantly higher in the age group of 1 – 3 years(60%) followed by 5 – 10 years(45.7%). The total number of injuries and the average number of injuries in boys were significantly higher than girls. The most common type of home injury was falls(54.6%) followed by burn injury(16.1%) and injury with sharps(11.8%). The environmental risk was assessed using standard and working definitions and found unsafe electrical points(97%), unsafe stairs(100%), unsafe short dining table(72%), unsafe kitchen with access to sharps(27.6%), access to active fire(23.6%), and unsafe furniture and objects(22%).Conclusions: Childhood unintentional home injuries are common in Upper Egypt. The total number of injuries and the average number of injuries in boys were significantly higher than girls. The falls were the most common type of injury among all age groups. The study revealed a significant burden of hazards for childhood injuries within their own homes.Recommendations: Implementation of safety and injury prevention measures that may involve legal changes, application of passive safety strategies, educating the parents and the children at schools, and financial support to poor families are important strategies for prevention of home injuries.
Keywords: children; home; unintentional injuries; Assiut governorate